Tunable dual-band bandpass filter / Wan Nurul Shuhada Wan Deraman - Wan Deraman, Wan Nurul Shuhada Wan Deraman (2016)
A tunable dual-band bandpass filter is presented. The filter topology consist of a coupled line connected directly to a line impedance with a same structure connected in parallel producing a dual-path filter design. Four additional capacitors is added to the design in order to shift the frequency response. The filter was designed at a center frequency of 2GHz and the capacitance value was varied to obtain the maximum shift in the frequency. The capacitor was converted into distributed element for EM simulation. Simulation results are presented to verify the concept